STATE OF THE MICROBIOLOGY ORAL CAVITY OF STUDENTS WITH DENTAL DISEASES - Kovach, Ilona; Shvartsnau, Elena; Vasilishina, Marta (Journal of Education, Health and Sport, 2015)
At the present time the urgent problem is the high prevalence of dental diseases among students. State of microecology of oral cavity, as well as risk factors connected with socio-economic conditions of life, behavioral features and habits, condition of somatic health have significant influence on oral tissues. That is why the aim of our study is to investigate the state of microbiocenosis of oral cavity in healthy people and students with dental diseases. Materials and methods of the study. The investigation of microbiocenosis of main biotopes of oral cavity in healthy people and students with dental diseases has been conducted in two age groups: 14 - 17 years and 18 - 22 years (67 persons). The platings have been taken on an empty stomach from 5 main points to determine the microbial landscape of different biotopes of oral cavity: 1 - oral fluid; 2 - mucous tunic of cheek along the line of molar teeth joining; 3 - mucous tunic of back on tongue (middle section); 4 – dental plaque from the vestibular surface of molars of lower jaw; 5 – liquid of dentogingival groove in the region of central incisors of the upper jaw (gingival fluid). Results. Conclusions. The picture of microbiocenosis of oral cavity in students with dental diseases, which take place on the background of somatic pathology and undergo the effect of risk factors, significantly differ from the same in healthy people. Besides the advantage of opportunistic and pathogenic microorganisms has been established, the number of which has significantly exceeded the data of indices of saprophytic microflora. The received digital data of the microbiological studies of the oral cavity in the students who have been diagnosed pathology of hard tissues of teeth and periodontal tissues on the background of somatic pathology and effect of risk factors indicate a significant dysbiosis of oral cavity, which is characterized by decreased activity of compensatory reactions and lack of possibility to resist microbial aggression because of the violation of colonization resistance, which can affect the course and treatment of basic dental diseases.